Focus on Vitamin D, Inflammation and Type 2 Diabetes - Andrade Chagas, Carlos Eduardo [UNESP]; Borges, Maria Carolina; Martini, Lgia Araujo; Rogero, Marcelo Macedo (Mdpi Ag, 2012)
The initial observations linking vitamin D to type 2 diabetes in humans came from studies showing that both healthy and diabetic subjects had a seasonal variation of glycemic control. Currently, there is evidence supporting that vitamin D status is important to regulate some pathways related to type 2 diabetes development. Since the activation of inflammatory pathways interferes with normal metabolism and disrupts proper insulin signaling, it is hypothesized that vitamin D could influence glucose homeostasis by modulating inflammatory response. Human studies investigating the impact of vitamin D supplementation on inflammatory biomarkers of subjects with or at high risk of developing type 2 diabetes are scarce and have generated conflicting results. Based on available clinical and epidemiological data, the positive effects of vitamin D seem to be primarily related to its action on insulin secretion and sensitivity and secondary to its action on inflammation. Future studies specifically designed to investigate the role of vitamin D on type 2 diabetes using inflammation as the main outcome are urgently needed in order to provide a more robust link between vitamin D, inflammation and type 2 diabetes.
Keywords: vitamin D; inflammation; diabetes